2021
DOI: 10.1007/s10924-021-02343-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Mechanical, Thermal and Water Absorption Behaviors of Cocos nucifera Shell Filler Reinforced Vinyl Ester Polymeric Composites

Abstract: Recently, natural filler reinforced polymer composites are important materials for various engineering applications. Hence, this present work focuses on utilization of Cocos nucifera shell powder (CNSP) as a filler in vinyl ester (VE) resin to produce particulate composite specimens. The particulate composite plates with various weights or filler contents from 5 to 30 wt.% were fabricated, using compression molding technique. The fabricated composites were subjected to tensile, flexural, impact, hardness, heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Although the hybrid filler concentration was below 15 wt%, it was found that void development was under control, which helped explain why the hybrid composites had good load-transfer capabilities. 27 On the other hand, a noticeably higher level of void development was seen when the filler percentage was raised from 15 to 24 wt%. Both flexural strength and flexural modulus appear to have significantly decreased as a result of a spike in filler reinforcement of over 24 wt%.…”
Section: Flexural Propertiesmentioning
confidence: 95%
“…Although the hybrid filler concentration was below 15 wt%, it was found that void development was under control, which helped explain why the hybrid composites had good load-transfer capabilities. 27 On the other hand, a noticeably higher level of void development was seen when the filler percentage was raised from 15 to 24 wt%. Both flexural strength and flexural modulus appear to have significantly decreased as a result of a spike in filler reinforcement of over 24 wt%.…”
Section: Flexural Propertiesmentioning
confidence: 95%
“…Vinyl polymers may generally be divided into three types: thermoplastics, thermosetting (vinyl ester), and elastomers. [3][4][5] In recent years, there has been a lot of interest in the usage of composite materials made of vinyl ester matrix and plantbased natural fiber reinforcements. In recent years, there has been a significant growth in the usage of natural fiber derived from plants as reinforcement in polymer matrix, because the natural fibers might take the role of synthetic fibers like glass, aramid, and carbon in polymeric materials due to their many benefits, including their ease of accessibility, low price, light in weight, and renewability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high hydrophilicity of plant fiber usually results in poor interfacial compatibility and mechanical properties when used as a reinforcing fiber. In addition, the composites are prone to water absorption and humidity aging in a humid environment, which greatly limits their wide range of industrial applications 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the composites are prone to water absorption and humidity aging in a humid environment, which greatly limits their wide range of industrial applications. 6,7 Many chemical and physical treatments have been developed for the modification of plant fiber. [8][9][10] For example, water treatment, alkali treatment, and heat treatment are used to remove pectin, fructose, lipids, and so forth.…”
Section: Introductionmentioning
confidence: 99%